Some statistical results on autoregressive conditionally heteroscedastic models - Gonçalves, Esmeralda (1998)
The aim of this paper is to present some statistical aspects of an order 1 autoregressive model with errors following a stationary and ergodic generalized threshold ARCH process. So, to analyse the precision of forecasts obtained with these models a probabilistic study will be done. Moreover, a consistent test for a general AR(1) model with errors following an ergodic white noise of null conditional median will be developed and adapted to our stochastic process.